Systematic theology. - Jenson, Robert W. (Oxford University Press, 1997)
Jensen begins this first of two volumes with an extended discussion of the nature and norms of theology. He then devotes the rest of the work to the identity and being of the biblical God, including classic Christological and soteriological questions most systems take up elsewhere.